Development of high performance fiber Raman amplication systems for optical fiber communications - Tang, Ming (2008)
Fiber Raman amplification (FRA) has been studied intensively since 1990s owing to its potential applications in fiber optic communication systems. Compared with the lumped erbium-doped fiber amplifier (EDFA), the distributed Raman amplification (DRA) takes the advantages that: 1) amplification can be provided at any frequency by simply changing the pump wavelength; 2) any existing transmission line can be upgraded directly to DRA by simply adding pumps accordingly; 3) the Raman gain distributed over tens of kilometers of transmission fiber provides in a superior end-ofsystem optical signal-to-noise-ratio (OSNR).